2010
DOI: 10.1038/tpj.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

A low-risk ZnT-8 allele (W325) for post-transplantation diabetes mellitus is protective against cyclosporin A-induced impairment of insulin secretion

Abstract: SLC30A8 encodes the b-cell-specific zinc transporter-8 (ZnT-8) expressed in insulin secretory granules. The single-nucleotide polymorphism rs13266634 of SLC30A8 is associated with susceptibility to post-transplantation diabetes mellitus (PTDM). We tested the hypothesis that the polymorphic residue at position 325 of ZnT-8 determines the susceptibility to cyclosporin A (CsA) suppression of insulin secretion. INS (insulinoma)-1E cells expressing the W325 variant showed enhanced glucose-stimulated insulin secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 40 publications
4
37
1
Order By: Relevance
“…Thus, the risk variant R325 is less active in transporting zinc in β cells than the protective variant W325 [77]. Similar data were also obtained by Kim et al using isolated secretory granules and radiotracers ( 65 Zn) [78]. …”
supporting
confidence: 79%
“…Thus, the risk variant R325 is less active in transporting zinc in β cells than the protective variant W325 [77]. Similar data were also obtained by Kim et al using isolated secretory granules and radiotracers ( 65 Zn) [78]. …”
supporting
confidence: 79%
“…It is also possible that introducing positive charges at the 'tip' of the protein may impair Zn 2+ transport through the protein. These possibilities have so far been assessed by overexpression of either variant in beta cells and imaging [15] or radioisotope-based studies on isolated granules [22]. In both cases, it was inferred that the W325 form was several-fold more active than the R325 form as a zinc transporter.…”
Section: Effects Of R325-w Substitution On Znt8 Functionmentioning
confidence: 99%
“…Thus, W325-ZnT8 expressing cells displayed higher levels of fluorescence than the R325-ZnT8-expressing cells when assessed with zinc probes (FluoZin-3 and Zinquin), showing at least partial co-localisation with insulin-containing granules. However, both approaches are subject to some limitations including (1) uncertainties as to the precise subcellular localisation of the fluorescent zinc probes used [15], and (2) potential clonal effects in studies of organelles isolated from cell lines [22]. Moreover, overexpression studies lead to at least some, albeit limited, incorporation of ZnT8 into the plasma membrane [15], and it has been speculated [23] that the W variant may be leakier in these assays, and thus a less active pump into the granule lumen.…”
Section: Effects Of R325-w Substitution On Znt8 Functionmentioning
confidence: 99%
“…Whereas, cells expressing ZnT8 R325 were suppressed by these drugs. This indicates that the structure of the ZnT8 variant W325 is important for protection against post-transplant diabetes [90]. Kang and colleagues reported that a polymorphism in the zinc transporter gene SLC30A8 confers resistance against post-transplant diabetes in renal transplant recipients [110].…”
Section: Znt7 and Znt8mentioning
confidence: 99%
“…Kang and colleagues reported that a polymorphism in the zinc transporter gene SLC30A8 confers resistance against post-transplant diabetes in renal transplant recipients [110]. In addition, Kim and colleagues reported that the ZnT8 R325 expressed in the INS-1E cell line showed reduced insulin content and secretion when treated with cyclosporine A (CsA) [90]. When ZnT8 variant W325 expression was treated with CsA, insulin content and secretion was not affected.…”
Section: Znt7 and Znt8mentioning
confidence: 99%